Connectivism, a new learning paradigm? - López De La Cruz, Edgardo Cristiam Iván (2021)
This article exposes and argues the learning theory called connectivism; a new learning paradigm that is beginning to be applied in this digital era, based on the interconnection of the nodes of a wide network of information and knowledge. The paper mentions some theories that gave rise to this new type of learning, as well as the foundations of this theory by its creators and advocates. The role of the teacher in this new form of learning and the importance of the student or participant node are explained; also, how this theory could evolve by implementing artificial intelligence and how intelligent connections could be achieved. Finally, the theory is projected to a new form of learning based on artificial education, resorting to intelligent nodes and conjecturing, in a certain way, the rupture of the indispensability of the teacher in this learning process.